Popeye - Williams, Robin, 1952 July 21-; Duval, Shelley 1949-; Paramount Pictures Corporation (Hollywood, Calif. : Paramount, 1989)
The legendary, beloved anvil-armed sailor of the seven seas comes magically to life in this delightful musical.
"1171."
VHS format.
Rated PG.
A videocassette release of the 1980 motion picture by Paramount Pictures Corporation.
Executive producer, C. O. Erickson ; producer, Robert Evans ; director, Robert Altman ; screenwriter, Jules Feiffer ; Music and lyrics, Harry Nilsson.
Robin Williams ; Shelley Duval.
Keywords: Motion pictures -- United States